Bioconvection flow of Carreau nanomaterial invoking Soret and Dufour impacts - Tasawar Hayat; Fatima Bibi; Aneeta Razaq; Sohail A Khan (Results in Engineering)
Background and objective: Thermal transport enhancement through nanomaterial flow has gained much attention of the investigators recently. Such attention is for applications in engineering, petroleum industries, geothermal engineering and pharmaceutical developments such as X-ray imaging, welding process, semiconductor material production, thermal storage system, electric cooling devices, drug delivery, magma solidification etc. In view of such interest here we analyze the bioconvective stretched flow of Carreau nanoliquid. Thermal, microorganism and mass convective constraints are considered. Gyrotactic microorganisms within presence of chemical reaction is considered. Variable thermal conductivity is considered. Dufour and Soret features are under consideration. Thermophoresis diffusion and random movement features are considered. Energy relation comprises heat generation and radiation. Methodology: Nonlinear dimensionless expressions are developed by employing suitable transformations. Numerical computations are obtained by implementation of Newton built in-shooting technique. Results: Performance of liquid flow, concentration, microorganism field, and thermal field is studied. Numerical values of quantities of engineering performance via influential parameters are explored. Larger Weissenberg number yield velocity increase. Reduction in velocity through bioconvection Rayleigh number is witnessed. Concentration and thermal field through solutal thermal Biot numbers have similar effect. An increment in thermal distribution and Nusselt number for Dufour number is detected. Increasing values of Soret number and chemical reaction correspond to decay in concentration. An augmentation in thermal transfer rate and temperature through radiation is noticed. An increment in density number against Peclet and bioconvection Lewis numbers is noticed.